Adhesion strength and anti-tumor agents regulate vinculin of breast cancer cells - Metsiou, Despoina Nektaria; Deligianni, Despina; Giannopoulou, Efstathia; Kalofonos, Haralabos; Koutras, Angelos; Athanassiou, George (Frontiers in Oncology, 2022)
The onset and the progression of cancer, is strongly associated with the dissipation of adhesion forces between cancer cells, thus facilitating the incessant attachment and detachment from the extracellular matrix (ECM) in order to move to the direction of metastasis. During this process, cancer cells undergo mechanical stresses and respond to these stresses with membrane deformation while induce protrusions to invade the surrounding tissues. The cellular response to mechanical forces is inherently related to the reorganization of cytoskeleton, the dissipation of cell-cell junctions and the adhesion to surrounding ECM. Moreover, the role of focal adhesion proteins and particularly the role of vinculin in cell attachment and detachment during migration is critical, indicating the tight cell-ECM junctions which favor or inhibit the metastatic cascade. The biomechanical analysis of these sequences of events may elucidate the tumor progression and the potential of cancer cells for migration and metastasis. In this work we focused on the evaluation of the spreading rate and the estimation of the adhesion strength between breast cancer cells-ECM prior to and post treatment with anti-tumor agents. Specifically, different tamoxifen concentrations, were used for ER+ breast cancer cells whilst even concentrations of Trastuzumab and Pertuzumab for HER2+ respectively. Analysis of cell stiffness indicated an increased elastic Young’s modulus post treatment in both MCF-7 and SKBR-3 cells. The results showed that the post treatment spreading rate was significantly decreased in both types of breast cancer suggesting a lower metastatic potential. Additionally, treated cells required greater adhesion forces to detach from ECM, thus preventing detachment events of cancer cells from ECM, and therefore, the probability for cell motility, migration and metastasis is confined. Furthermore, post detachment and post treatment vinculin levels were increased, indicating tighter cell-ECM junctions, hence limiting the probability for cell detachment and, therefore, cell motility and migration.